Makna dan Fungsi Sawah Lodok di Kampung Meler Desa Meler Kecamatan Ruteng Kabupaten Manggarai Nusa Tenggara Timur - Sumardi, Fransiskus; Sukardja, Putu (Humanis; Vol 18 No 1 (2017))
Meler is the name of a village located in the Meler village, district of Ruteng, regency of Manggarai, Flores, East Nusa Tenggara are still maintaining the fields of lodok. There are formulations of the problem in researching, namely: the first one, what types or forms of lodok fields .The second, how the function of lodok fields. The third, what meaning of symbolic of lodok fields in the Meler village. The porpose of this researching are: the first, to know the fields of lodok. The second, to understand the function of lodok fields.And the third, to explain the meaning of symbolic the lodok fields. This searching uses three of theories to peel the problems which studied, namely, the first: theory of meaning denotation and connotation of Roland Barthes, the second, functional theory of Malinowki, and the second, functional theory of Robert K. Marton. The concept used in this researching are the concept of field, symbol, and lingko. The researched method used areetnography research model that include into the qualitative searching, observation, detailed interview, and literature studies. The analysis of data used were descriptive and qualitative analysis. The last result of this researching are function of the lodok fields are social, economy, religion, manifest, and latent. The meaning of lodok fields, are connotation, and denotation. A long with era development, the meaning of the fields experiencing dynamics which influenced by two factors: internal factors and external factors
Keywords: Meaning, Function and Symbol the Fields of Lodok